Combinatorial codon-based amino acid substitutions - Yáñez, Jorge (Oxford University Press, 2004)
Twenty Fmoc-protected trinucleotide phosphoramidites representing a complete set of codons for the natural amino acids were chemically synthesized for the first time. A pool of these reagents was incorporated into oligonucleotides at substoichiometric levels to generate two libraries of variants that randomly carry either few or many codon replacements on a region encoding nine amino acids of the bacterial enzyme TEM-1 β-lactamase. Assembly of the libraries was performed in a completely automated mode through a simple modification of ordinary protocols. This technology eliminates codon redundancy, stop codons and enables complete exploration of sequence space for single, double and triple mutations throughout a protein region spanning several residues. Sequence analysis of many non-selected clones revealed a good incorporation of the trinucleotides, producing combinations of mutations quite different from those obtained using conventional degenerate oligonucleotides. Ceftazidime-selection experiments yielded several never before reported variants containing novel amino acid combinations in the β-lactamase omega loop region.